Social work and family violence: theories, assessment, and intervention - McClennen, Joan C. (Springer Publishing Company, 2017)
Preface -- Acknowledgments -- Introduction to family violence -- Introduction to child maltreatment -- Identifying and investigating child maltreatment -- Criminal justice and child maltreatment -- Consequences of child maltreatment and continuum of care -- Assessment and intervention in child maltreatment -- Child witnesses of intimate partner violence -- Introduction to intimate partner violence -- Dynamics of intimate partner violence -- The criminal justice system and intimate partner violence -- Assessment and intervention with victims of intimate partner violence -- Perpetrators of intimate partner violence -- Intimate partner violence among diverse and at-risk populations -- Introduction to older adult abuse -- Screening and investigation of older adult abuse -- Older adult abuse : assessment and intervention -- Prevention of family violence